2011
DOI: 10.1007/s00726-011-1088-7
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and the metabolism of branched-chain amino acids in humans

Abstract: Peripheral resistance to insulin action is the major mechanism causing the metabolic syndrome and eventually type 2 diabetes mellitus. The metabolic derangement associated with insulin resistance is extensive and not restricted to carbohydrates. The branched-chain amino acids (BCAAs) are particularly responsive to the inhibitory insulin action on amino acid release by skeletal muscle and their metabolism is profoundly altered in conditions featuring insulin resistance, insulin deficiency, or both. Obesity, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
111
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 89 publications
9
111
2
1
Order By: Relevance
“…At present, the role of BCAAs and their implications in the development of IR remain controversial. Indeed, in obese or overweight individuals, BCAAs have been reported to induce IR (49).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the role of BCAAs and their implications in the development of IR remain controversial. Indeed, in obese or overweight individuals, BCAAs have been reported to induce IR (49).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that a cluster of metabolites comprised of the branched-chain amino acids (BCAA) leucine (Leu), isoleucine (Ile), and valine (Val) and their metabolites, as well as the aromatic amino acids (AAA) tyrosine (Tyr) and phenylalanine (Phe), are strongly associated with obesity and insulin resistance in humans (1,10,29,43,67,78). Moreover, a very similar metabolite cluster predicts incident type 2 diabetes in longitudinal studies in humans (64) and, when measured at baseline in obese subjects, also predicts improvement in insulin sensitivity in response to a dietary/behavioral weight loss intervention (63).…”
mentioning
confidence: 99%
“…Thus it is quite natural that plasma levels of BCAAs increase in patients of type 2 diabetes [4][5][6][7] because the metabolism of such amino acids are impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Branched-chain amino acids concentrations have been shown to be elevated in response to overnutrition and can affect insulin sensitivity and secretion [3]. Number of human studies have consistently indicated that concentrations of BCAAs in plasma and urine are associated with insulin resistance [4][5][6][7]. We recently examined relationship between various foods uptakes and body mass index (BMI) and various plasma parameters in Japanese young and old men and women [8].…”
Section: Introductionmentioning
confidence: 99%